2013
DOI: 10.1002/cctc.201300523
|View full text |Cite
|
Sign up to set email alerts
|

Piperylene—A Versatile Basic Chemical in Catalysis

Abstract: Today’s industrial chemistry heavily relies on petrochemical feedstocks, and most of the starting compounds are available from the convenient steam cracking of hydrocarbons. In particular, the short‐chain key compounds ethene and propene take center stage. In addition, low‐molecular‐weight conjugated dienes such as butadiene and isoprene have remarkable importance in the production of polymers and fine chemicals. Another, so far clearly underrated, short‐chain conjugated diene is piperylene (1,3‐pentadiene), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 159 publications
0
22
0
Order By: Relevance
“…Not only the conversion of the alkyne was better, but the selectivity in favor of the 2,3-diphenylbuta-1,3-diene was excellent since 2a' could not be detected. Optimization of the reaction in toluene revealed that 100 • C, 17 h were the optimum experimental conditions whereas a higher pressure of ethylene had a negative effect inhibiting the catalytic reaction, and lower catalyst loading led to decreased activity (Table 1, entries [12][13][14][15]. The first generation catalyst III utilized in the conditions of entry 7 led to only 10% conversion [60] and a high proportion of hydrovinylation product 2a'.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the conversion of the alkyne was better, but the selectivity in favor of the 2,3-diphenylbuta-1,3-diene was excellent since 2a' could not be detected. Optimization of the reaction in toluene revealed that 100 • C, 17 h were the optimum experimental conditions whereas a higher pressure of ethylene had a negative effect inhibiting the catalytic reaction, and lower catalyst loading led to decreased activity (Table 1, entries [12][13][14][15]. The first generation catalyst III utilized in the conditions of entry 7 led to only 10% conversion [60] and a high proportion of hydrovinylation product 2a'.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the classical [4 + 2] cycloadditions, 1,3-butadiene itself and aliphatic 1,3-butadiene substrates have been efficiently transformed via transition metal-catalyzed reactions. Among them, ruthenium-catalyzed addition of aldehydes [5] and olefin metathesis [6], nickel-catalyzed multicomponent coupling with alkynes or aldehydes and dimethylzinc in the presence of carbon dioxide [7,8], rhodium-catalyzed asymmetric [4 + 3] cycloaddition with vinylcarbenoids [9], palladium-catalyzed telomerization with various nucleophiles [10][11][12], hydroamination [13,14] and hydroamidocarbonylation [15], are representative examples. However, monoarylated 1,3-dienes have been used for triflic acid-catalyzed synthesis of indenes [16], ruthenium-catalyzed isomerization [17], palladium-catalyzed hydroarylation with boronic esters [18], cobalt-catalyzed hydrosilylation [19], asymmetric hydrovinylation with ethylene [20] and enantioselective cycloaddition with internal alkynes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Reactions were conducted at room temperature using isoprene, Ni(cod) 2 catalyst, triethylborane, and N,O-acetals under nitrogen atmosphere. Isoprene reacted at the C1 position with N,O-acetals and underwent homoallylation to provide hydroxybishomoallylamines.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-coupling of organometallic compounds with aromatic halides, as well as allylation and vinylation of carbonyls, is widely utilized for the synthesis of physiologically active molecules and fine chemicals [2]. Compared to catalytically C-C bond transformations involving allylation and vinylation, homoallylation of carbonyls providing bis-homoallyl alcohols have serious limitations, which may be due to the unavailability and low stability of homoallyl anion species that can react with electrophiles [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits potential chemical properties, however, till now it is mainly used for hydrogenation to n-pentane followed by subsequent isomerisation to iso-pentane which is used as a gasoline additive. [7] Using this underrated compound, the approach of this contribution was to convert piperylene into valuable ester compounds, by usage of common bulk chemicals.…”
Section: Introductionmentioning
confidence: 99%